(untitled) (Indian Journal of Traditional Knowledge (IJTK), 2023)
Worldwide there is increased shift towards usage of traditional medicine in patients of chronic diseases like Cardio Vascular Disorders. In India, these medicines are used concurrently. Objective of the study was to ascertain prevalence and effect of concurrent traditional drug therapy with standard pharmacotherapy in patients with CVD. The present study used a cross sectional study design to assess the prevalence and a prospective cohort design to assess the effect of concurrent Ayurvedic medicines with standard pharmacotherapy in terms of quality of life. After screening 600 patients, 128 were found taking such medicines. Out of these, 100 were recruited as cases (Group-I), while 100 who were matched in terms of age, body mass index, ejection fraction, and receiving standard therapy only were recruited as controls (Group-II). Assessment parameters included demographic, biochemical, ejection fraction through echocardiography, distance covered in six Minute walk Test (6MWT), Quality of Life (QOL) through Kansas City Cardio-myopathy Questionnaire (KCCQ) and Seattle Angina Questionnaire (SAQ) with follow up at 6 months. Prakriti as mentioned in Ayurveda was also assessed using a questionnaire. Both groups were comparable at base line. Total 87 in Group-I and 91 in Group-II completed the study. Further, 76% patients were diagnosed with heart failure (HF) and 24% with coronary artery disease (CAD). There was no change in distance covered in 6MWT in both HF or CAD groups. But there was improvement in all cases in domains of KCCQ and SAQ as compared to controls. To conclude, concurrent use of traditional medicine with standard conventional care in CVD may improve quality of life in cardiovascular disorders.